Izzivi in ovire sonaravnega kmetijstva na Dravskem polju - Breg Valjavec, Mateja (Geografski vestnik, 2007)
The Dravsko polje alluvial gravel plain is the area of the intensive agriculture with the prevailing cultivation of maize and other crops for the needs of cattle breeding. The excessive usage of fertilizers and agrochemicals is burdening the ground water, the only water source for the residents of the Kidričevo municipality. The results of research show that the vulnerability of the environment is critical in many places as far as the ground water is concerned, and this still has not encouraged the sustainable farming. The most endangered are the areas where the pollution with nitrides and pesticides is the highest and the self-protective capacity of the ground water the lowest. The only solution to this problem is to restructure the intensive agriculture into integrated and especially into organic farming. The article shows, on grounds of a comprehensive environment and socio-economic analysis, the possibilities, obstacles and a spatial model of a sustainable development of agriculture in this part of the Dravsko polje plain.
Keywords: agrarna geografija; agriculture; kmetijstvo; sonaravni razvoj; gnojenje; onesnaževanje okolja; vodni viri; Dravsko polje; Slovenia; Slovenija